2011
DOI: 10.1080/11250001003639590
|View full text |Cite
|
Sign up to set email alerts
|

Age structure and body size of two populations of the rice frogRana limnocharisfrom different altitudes

Abstract: Identifying the patterns of body size and age in relation to altitudes may help us to understand the evolution of life history of organisms. With this view, we compared the demographic traits of a subtropical frog, Rana limnocharis, between populations from southwestern China located at two altitudes (310 and 800 m) with distinct mean annual temperature (17.1°C and 15.2°C). Overall, frogs from the higher altitude tended to be significantly larger in body size. Within each population, adult females were markedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 42 publications
(65 reference statements)
2
15
0
Order By: Relevance
“…Previous studies showed that SSD in anurans can be explained by age differences between males and females [16,32,37-49]. Our results demonstrate a correlation between SSD and SAD across 39 species, identifying SAD as a main factor contributing to the extent of SSD across species.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies showed that SSD in anurans can be explained by age differences between males and females [16,32,37-49]. Our results demonstrate a correlation between SSD and SAD across 39 species, identifying SAD as a main factor contributing to the extent of SSD across species.…”
Section: Discussionsupporting
confidence: 69%
“…The Asian grass frog (Fejervarya limnocharis) inhabits a wide range of habitats in China below an elevation of 2000 meters. The egg-laying period lasts from early April to September, during which males actively search for females and attract them with courtship calls (Fei & Ye, 2001;Liao et al, 2011). The activity and growth period of F. limnocharis is markedly shaped by environmental temperature and the growth season, which in turn is determined by altitude as well as latitude (Liao, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Skeletochronology technique was successfully applied for femur bone of F. cancrivora, which improved the results that had been done by Kusrini and Alford (2006) for the same species. The success of the skeletochronology technique also proved in F. limnocharis (Liao et al 2011;Pancharatna and Deshpande 2003;Phadmacanty et al 2018) which is a close relative to F. cancrivora. The number of LAG compared with the length of SVL at the pre-adult stage, adult males and adult females showed accurate results with a strong correlation between the two parameters.…”
Section: Discussionmentioning
confidence: 85%
“…Bone parts that are commonly used in skeletochronological research are the phalanx bones (Eden et al 2007;Guarino and Eresmis 2008;Hasumi 2010;Liao and Lu 2010a;Liao and Lu 2010b;Liao et al 2011;Morrison et al 2004;Olgun et al 2005;Oromi et al 2012); but the femur can also be used (Castanet et al 1996;Kutrup et al 2005;Sinsch and Dehling 2017). However, Pancharatna and Deshpande (2003) reported that tibia and fibula bones can be used forskeletochronological research without any significant difference result in one individual frog.…”
Section: Introductionmentioning
confidence: 99%